(untitled) - Leblond, Geoffrey (New York, 1990)
A practical guide to AT and Ts complex UNIX V.3., explaining the system's features and functions. Early chapters cover such elements as basic program commands, using files and directories, and editing and text processing. The LeBlond Group then shows how to use the three "shells" included in the UNIX system with an emphasis on solving real-life problems and increasing productivity. It also covers program development, system administration and the utility programs included with UNIX
Keywords: UNIX,UNIX; Computer file,Tập tin máy tính